Lipophagy and Alcohol-Induced Fatty Liver - Yang, Li; Yang, Changqing; Thomes, Paul G.; Kharbanda, Kusum K.; Casey, Carol A.; McNiven, Mark A.; Donohue, Terrence M. (Frontiers in Pharmacology, 2019)
Abstract: This review describes the influence of ethanol consumption on hepatic lipophagy, a selective form of autophagy during which fat-storing organelles known as lipid droplets (LDs) are degraded in lysosomes. It is well established that excessive drinking accelerates intrahepatic lipid biosynthesis, enhances uptake of fatty acids by the liver from the plasma and impairs hepatic secretion of lipoproteins. All three contribute, in part, to alcohol-induced fatty liver (steatosis). Here, our principal focus is on lipid catabolism, specifically the impact of excessive ethanol consumption on lipophagy, which also influences alcohol-induced steatosis. Our review includes findings, which indicate that chronic ethanol consumption retards lipophagy, thereby exacerbating steatosis. This is important because alcohol-induced fatty liver was formerly regarded as a benign consequence of heavy drinking. Now, it is almost universally viewed as the ‘first hit’ in the spectrum of alcohol-induced pathologies that, with continued drinking, progresses to more advanced liver disease, liver failure, and/or liver cancer. Complete lipid droplet breakdown requires that LDs be digested to release their high-energy cargo, consisting principally of cholesteryl esters and triacylglycerols (triglycerides). These undergo lipolysis, yielding free fatty acids that are oxidized in the mitochondrion to generate energy. Our review will describe recent findings from our laboratories and others on the role of lipophagy in LD catabolism and how chronic heavy drinking affects this process. Throughout most of this review, the terms “autophagy” and “lipophagy” will sometimes be used interchangeably, as the two are closely-linked processes, in which LDs are degraded either “in bulk”, along with other cellular constituents, or are selectively taken up and degraded